Integrative Taxonomy Reveals Molicola uncinatus and Gymnorhynchus gigas (Cestoda: Trypanorhyncha) Coinfection in the Atlantic Pomfret Brama brama From the Mediterranean Sea, With Notes on the Phylogenetic Position of G. gigas Within the Family Gymnorhynchidae - Santoro, Mario; Palomba, Marialetizia; Aco Alburqueque, Renato; Mattiucci, Simonetta (Frontiers in Veterinary Science, 2022)
The cestode family Gymnorhynchidae Dollfus, 1935 (Trypanorhyncha) comprises three genera and six valid species that are typically intestinal parasites of large pelagic sharks. Members of Gymnorhynchidae show a wide geographic distribution and represent a global sanitary concern because as larvae they infect the edible flesh of several commercially important fishes with some species having allergenic potential. Larval Gymnorhynchidae collected from the muscles of the Atlantic pomfret Brama brama from various localities in the Mediterranean Sea were identified and characterized by combining traditional morphology, scanning electronic microscopy, and molecular analyses using newly generated nuclear 18S and 28S rRNA sequences. Overall, 98 larvae were collected from 20 (100%) Atlantic pomfrets (intensity of infection: 4.9; range: 1–12). High-quality sequences were obtained for 54 larvae. Of these, 11 and 43 larvae were identified as Molicola uncinatus and Gymnorhynchus gigas, respectively. The phylogenetic analysis showed the existence of three main clades within Gymnorhynchidae. The first included species of G. gigas and M. uncinatus from the Mediterranean and Atlantic; the second and third major clades included an unidentified species of Molicola from the Indian Ocean and specimens of Gymnorhynchus isuri from the Mediterranean and Atlantic, respectively. Finally, Chimaerarhynchus rougetae was the basal and most diverging taxon. The phylogenetic analysis suggested that G. gigas is more closely related to the members of Molicola. We demonstrated the coinfection of M. uncinatus and G. gigas from all localities studied and extended the intermediate hosts and geographical range of M. uncinatus by including the Atlantic pomfret and the Tyrrhenian and Ionian Seas, respectively. The present results supported the previous proposal that G. gigas and Molicola species should be included in the same genus. Our study demonstrated the usefulness of the integrative taxonomy for the unequivocal recognition of larval trypanorhynch species, resolving the current difficulties in the taxonomy, and elucidating the poorly known ecological and biological aspects of members of Gymnorhynchidae.